Довідкові регіональні видання з геральдики - Іщенко, Я. (Історико-географічні дослідження в Україні, 2004)
Одним з джерел інформації про наявність історичних гербів міст України та новотворів 60-х–80-х рр. ХХ ст. виступає «Алфавитный каталог городов, поселков, сел, губерний и областей России, СНГ, бывших союзных республик СССР, имеющих старые и современные гербы». Автор рецензії проаналізував принципи укладання подібних джерел інформації, зробив свої зауваження та висловив побажання щодо їх вдосконалення. «Alphabetical catalogue of towns, settlements, villages,
provinces and regions of Russia, Commonwealth of Independent
States, former Soviet Republics of the USSR, which have old
and present-day coat of arms» is one of the sources that gives
information about historical coat of arms and newly formed
emblems of Ukraine during 60th – 80th of XX century. The
author of the review analysed the structure of similar sources and
made her remarks and suggestion regarding to its improvement.